Detection of short X-ray pulses excited by an atmospheric-pressure discharge of nanosecond duration in air; Instruments and Experimental Techniques; Vol. 50, iss. 5 - Aizenshtat G. I.; Baksht E. Kh.; Kostyrya I. D.; Lelekov M. A.; Lomaev M. I.; Nadreev, I. I.; Nam I. F. Irina Feliksovna; Rozhnev M. A.; Rybka D. V.; Ryabkov S. A.; Tarasenko V. F. Victor Fedotovich; Tolbanov O. P.; et al. (2007, 2007)
Title screen